2008
DOI: 10.4049/jimmunol.180.12.8250
|View full text |Cite
|
Sign up to set email alerts
|

ALeishmaniaOrtholog of Macrophage Migration Inhibitory Factor Modulates Host Macrophage Responses

Abstract: Parasitic organisms have evolved specialized strategies to evade immune defense mechanisms. We describe herein an ortholog of the cytokine, macrophage migration inhibitory factor (MIF), which is produced by the obligate intracellular parasite, Leishmania major. The Leishmania MIF protein, Lm1740MIF, shows significant structural homology with human MIF as revealed by a high-resolution x-ray crystal structure (1.03 Å). Differences between the two proteins in the N-terminal tautomerization site are evident, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
115
0
14

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(135 citation statements)
references
References 56 publications
6
115
0
14
Order By: Relevance
“…Notably, parasite MIF orthologs have been identified in several evolutionarily distant species of helminthic and protozoan pathogens (29). The close structural similarities between these parasite orthologs and mammalian MIF, together with evidence that these orthologs bind the MIF receptor (58,59), suggest that parasite proteins also may act to modulate the adaptive immune responses of their hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, parasite MIF orthologs have been identified in several evolutionarily distant species of helminthic and protozoan pathogens (29). The close structural similarities between these parasite orthologs and mammalian MIF, together with evidence that these orthologs bind the MIF receptor (58,59), suggest that parasite proteins also may act to modulate the adaptive immune responses of their hosts.…”
Section: Discussionmentioning
confidence: 99%
“…The T. vaginalis genome (www.trichdb.org) encodes a single MIF homolog (Tvag_219770). This protein, TvMIF, has 31% identity to HuMIF and contains all nine invariant residues (33) found in other eukaryotic MIFs (marked in red in Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that several parasitic eukaryotes encode MIF-like proteins with considerable structural and biological similarity to their mammalian hosts (31)(32)(33)(34). These parasite MIF proteins have been shown to modulate host immune Significance Prostate cancer is the most common nonskin cancer in America and the fifth most common cancer worldwide.…”
mentioning
confidence: 99%
“…The existence of two genes that exhibit signifi cant sequence identity with mammalian MIF in the genome of Leishmania genus suggests a physiological role for macrophage migration inhibitory factor-like protein (MIF1 and MIF2) in the parasite life cycle and the establishment of these orthologues as virulence factors [24][25][26] . To date, the biological activities described for the L. major MIF orthologues include the induction of macrophage migration and an anti-apoptotic activity that could be responsible for the intracellular persistence of Leishmania in macrophages; thus, these MIF orthologues may be related to the clinical outcome 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Two genes that encode orthologues of human macrophage migration inhibitory factor (MIF) in the Leishmania genus have been described [24][25][26] . Human MIF is a major mediator of infl ammation.…”
Section: Introductionmentioning
confidence: 99%